Documentary theatre as a means of raising awareness of racist phenomena among teachers - Vassilopoulos, Panos (Education & Theatre, 2023)
This article reports on a case study related to the impact of documentary theatre on teachers’ perceptions and the possible influences on and changes in their behaviour as a result of raising their awareness of racism issues. The study includes action research conducted in the school year 2021–2022 in a series of experiential workshops involving theatre in education programmes. The teachers who participated in the research served in schools of primary and secondary education in the municipality of Aigialeia in the region of Achaia, Peloponnese. Group members used primary sources, real events and personal testimonies to approach various forms of discrimination and racist behaviour.